A Critical Analysis on Characterizing the Meditation Experience Through the Electroencephalogram - Deolindo, Camila Sardeto; Ribeiro, Mauricio Watanabe; Aratanha, Maria Adelia; Afonso, Rui Ferreira; Irrmischer, Mona; Kozasa, Elisa Harumi (Frontiers in Systems Neuroscience, 2020)
Meditation practices, originated from ancient traditions, have increasingly received attention due to their potential benefits to mental and physical health. The scientific community invests efforts into scrutinizing and quantifying the effects of these practices, especially on the brain. There are methodological challenges in describing the neural correlates of the subjective experience of meditation. We noticed, however, that technical considerations on signal processing also don't follow standardized approaches, which may hinder generalizations. Therefore, in this article, we discuss the usage of the electroencephalogram (EEG) as a tool to study meditation experiences in healthy individuals. We describe the main EEG signal processing techniques and how they have been translated to the meditation field until April 2020. Moreover, we examine in detail the limitations/assumptions of these techniques and highlight some good practices, further discussing how technical specifications may impact the interpretation of the outcomes. By shedding light on technical features, this article contributes to more rigorous approaches to evaluate the construct of meditation.